Higgs decay into massive b-quarks at NNLO QCD in the nested soft-collinear subtraction scheme - Arnd Behring; Wojciech Bizoń (Journal of High Energy Physics)
Abstract We present a fully differential description of a decay of a scalar Higgs boson into massive b-quarks valid at next-to-next-to-leading order (NNLO) in perturbative quan- tum chromodynamics (QCD). We work within the nested soft-collinear subtraction scheme extended to accommodate massive partons. We include the loop-induced contribution in- volving a Higgs coupling to a top quark. We test our calculation against results existing in the literature, comparing the predictions for the total decay width and jet rates.